PLANING MEMASYARAKATKAN KHATMILQUR’AN DALAM MEMANFAATKAN WHATSAPP - Fifi Julfiati; Kusumawati; HAM Idris Tumenggung (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Research (PKM) focuses on the effort to adapt digital technology, particularly the use of WhatsApp, as a managerial medium within the context of Islamic education. Its primary aim is to devise structured planning for the execution of Khatmil Qur'an (Quran completion) at TPQ Arrizqy in May 2025. The project, involving lecturers and students from Pamulang University, focused on two critical aspects: the effectiveness of WhatsApp group-based planning and the measurement of student comprehension levels through parental feedback mechanisms post-program. The PKM methodology was implemented through four sequential phases: field observation, detailed planning (curriculum design and scheduling), logistical preparation, and the execution stage (in the form of discussions and workshops). The results indicate that the WhatsApp platform proved vital in structuring the memorization or tadarus cycle (3, 6, or 12-month periods) and ensuring efficient real-time communication and coordination among teachers, parents, and students (santri). Further post-activity evaluation suggested an increase in parental awareness and understanding regarding their children's Al-Qur'an reading competency progress, concurrently boosting community involvement. The study concludes that the integration of digital applications can serve as a means of modernizing religious practices in education, provided that essential Islamic values are preserved, and recommends broader implementation of similar technology in other Islamic educational institutions. Keywords: Digitalization of Islamic Education, Khatmil Qur'an, WhatsApp Communication Technology